Development of primary school pupils’ cognitive abilities in the activity and cooperative mathematics - Kiseliovas, Arkadijus; Kiseliova, Danutė (Lietuvos matematikos rinkinys, 2000)
The mathematics set for primary school in the World of Mathematics is treated as activity, communication and cooperative mathematics developing pupils’ cognitive abilities. The importance of mathematics activity verbalization and its relations with different child orientated educational systems taking into account the pupil’s interests, inclinations, wish to communicate and study have been emphasized.